Susceptibility to R-pyocins of Pseudomonas aeruginosa clinical isolates from cystic fibrosis patients. (24th July 2018) - Redero, Mar; López-Causapé, Carla; Aznar, Javier; Oliver, Antonio; Blázquez, Jesús; Prieto, Ana I
Abstract: Background: The appearance and dissemination of MDR among pathogenic bacteria has forced the search for new antimicrobials. Bacteriocins have been proposed as potential alternatives for the treatment of infections due to multiresistant strains. Objectives: To analyse the activity of R-pyocins against clinical isolates of Pseudomonas aeruginosa from patients with cystic fibrosis and other sources and evaluate them as a potential adjuvant or alternative to the current antibiotic treatment. Methods: The activity of R-pyocins against 150 strains of P. aeruginosa isolated from patients with cystic fibrosis or bacteraemia was studied through spot assay. Interactions between R-pyocins and antipseudomonal agents were quantitatively studied by the chequerboard method. Results: The proportion of P. aeruginosa isolates susceptible to R-pyocins was found to be higher in cystic fibrosis isolates compared with bacteraemia isolates (79.41% versus 50%). Moreover, no interactions were found between common antipseudomonal agents and R-pyocin susceptibility, except for the ST175 high-risk clone. Conclusions: Our results highlight the possibility of using R-pyocins as therapeutic agents, alone or as adjuvants, against P. aeruginosa in cystic fibrosis.